Structural limits to effective environmental activism: Post‐neoliberal development, extractive imperative and authoritarianism in Ecuador - Murat Arsel; Lorenzo Pellegrini (Geo: Geography and Environment)
Abstract With the election of President Rafael Correa in the 2006 elections, Ecuadorian environmentalists became influential policymaking actors. Agenda‐setting successes were followed by their decisive contribution to determining legislative content and its passing. However, the moment of alliance between environmentalists and Correa proved to be temporary. Environmentalists returned to a more adversarial posture in relation to the state and its approach to constructing a post‐neoliberal development model that relied on the intensification of primary commodity extraction. Their efficacy in shaping environmental policy making and implementation declined and their activities against oil and mining extraction were met by increasingly authoritarian responses by the state. Structural constraints emerging from the global political economy of environment and development were ultimately decisive in the rise of authoritarianism and the reversal of the agenda of the environmentalists.